Freezing tissues pre-homogenisation reduces degradation and yields improved quality RNA in the mouse lung - Mohd Kamal, Khairunnisa; Ghazali, Ahmad Rohi; Selvarajah, Gayathri Thevi; Ab Mutalib, Nurul Syakima; Abu, Nadiah; Chua, Eng Wee; Masre, Siti Fathiah (Elsevier, 2025)
Ribonucleic acid (RNA) extraction requires meticulous sample handling to ensure purity and integrity. Although a variety of commercial kits are available, along with optimised protocols, pre-extraction sample processing remains a challenging procedure, especially with tissue samples. In our brief report, we describe the beneficial impact of freezing tissues before homogenisation on the quality of RNA extraction. Lung tissues were freshly excised from mice and homogenised with or without prior quick freezing in a freezer. Then, RNA was extracted according to the protocol provided with a commercial column-based RNA extraction kit. RNA quality was analysed by UV absorbance and agarose gel electrophoresis. We found that the frozen tissues yielded better-quality, more intact RNA than the non-frozen tissues, possibly due to lower temperatures during homogenisation. “Smearing”, indicative of RNA degradation, was visible in some of the non-frozen samples. The extra quick-freezing step provides a simple and affordable method for preserving high-quality RNA, especially from tissue samples. Further comparisons can be made to determine whether the observed benefits extend to other tissue types or to quantitative polymerase chain reaction (qPCR) analysis in gene expression studies.